Veratrilla baillonii Franch Could Alleviate Lipid Accumulation in LO2 Cells by Regulating Oxidative, Inflammatory, and Lipid Metabolic Signaling Pathways - Huang, Xian-ju; He, Cai-jing; Liang, Shuai; Wang, Jing; Li, Jun; Yang, Guang-zhong; Zhao, Zhang (Frontiers in Pharmacology, 2020)
Based on the pathological theory of lipid metabolism and using network pharmacology, this study was designed to investigate the protective effect of water extract of V. baillonii (WVBF) on non-alcoholic fatty liver disease (NAFLD) model using LO2 cells and to identify the potential mechanism underlying the effect. The components of V. baillonii were identified from the public database of Traditional Chinese Medicine Systems Pharmacology Database (TCMSP). Cytoscape software was used to construct the related composite target network. Then, GO and KEGG analysis were carried out for critical nodes. The BioGPS database was used to determine the distribution of the target in tissues and organs. Moreover, the inhibitory effect of V. baillonii was further investigated using an in vitro hepatocyte NAFLD model. Fourteen active components were then selected from the 27 known compounds of V. baillonii. The targets of gene enrichment analysis were mainly distributed in the lipid catabolism-related signaling pathway. Network analysis revealed that five target genes of TNF, MAPK8, mTOR, NF-ĸB, and SREBP-1c were key nodes and played important roles in this process. Organ localization analysis indicated that one of the core target site of V. baillonii was liver tissue. The results of the in vitro study revealed that WVBF can alleviate the inflammatory response and lipid accumulation in LO2 hepatocytes by inhibiting oxidative stress and the adipocytokine signaling pathway. Genes and proteins related to the lipid synthesis, such as SREBP-1C, ACC, and FASN, were significantly decreased, and PPARα expression is significantly increased with WVBF administration. In conclusion, V. baillonii may regulate local lipid metabolism and attenuate oxidative stress and inflammatory factors through the PPARα/SREBP-1c signaling pathway. The present study also indicates that multiple components of V. baillonii regulate multiple targets and pathways in NAFLD. The findings highlight the potential of V. baillonii as a promising treatment strategy for nonalcoholic fatty liver injury.